Heavy metal fraction, pollution, and source-oriented risk assessment in biofilms on a river system polluted by mining activities. (May 2023) - Xu, Hansen; Li, Chunyan; Wen, Chen; Zhu, Shijun; Zhu, Shiqi; Li, Nihong; Li, Rufei; Luo, Xia
Abstract: The Lanping Pb–Zn mine is the largest source of Pb and Zn ores in China, thus posing a great threat to local ecosystems and human health. A total of seven heavy metals (Zn, Pb, Ni, Cu, Cr, Cd, and As) in the Bijiang River near the Pb–Zn mine were measured in winter and summer to assess their spatial–temporal enrichment, ecological risk, and source-oriented health risk in periphytic biofilms. Positive matrix factorization (PMF) receptor model and clustering analysis were used to quantitatively identify pollution sources. The results of PMF were then imported into the health risk assessment to further determine the carcinogenic and noncarcinogenic risks of various pollution sources. The results indicated distinct seasonal patterns in metal concentrations, with much higher concentrations in winter. Sites near the Pb–Zn mine tailing reservoir exhibited higher metal contamination levels than other sites. A strong correlation between the enrichment factor and the levels of nonresidual fraction suggested that anthropogenic inputs were the main source of these metals. Mining industries (Cd, Zn, and Pb), natural sources (As, Ni, and Cu), and agricultural activities (Cr) were the primary sources of heavy metal pollution in biofilms, accounting for 44.43%, 33.32%, and 22.26% of the total metal accumulation, respectively. Moreover, the carcinogenic and noncarcinogenic risks via dermal contact of the studied elements in biofilms were typically acceptable. Notably, as concentration was the main factor influencing these risks in children and adults. This study provides evidence that natural epilithic periphyton may be a potential metal biomonitor in aquatic systems and provide supporting information for effective source regulation. Graphical abstract: Image 1 Highlights: Mining activities were the main anthropogenic sources. As showed the highest ecological risk due to its high concentration and toxicity. Cd, Zn, Pb were derived mainly from mining activities while Cr was mainly attributed to agricultural activities. As had the most potential for impacting human health.